CLASSIFICATION OF HOUSEHOLD VIOLENCE (KDRT) CASES BASED ON CAUSING FACTORS USING CLUSTERING METHOD - Aprilianda, Dinda; Saragih, Rusmin; Saripurna, Darjat (Yayasan Bina Internusa Mabarindo, 2023)
Domestic violence is a violation of human rights and a crime against human dignity and is a form of discrimination. Therefore, no matter how small the violence committed can be reported as a criminal act that can be processed by law. The Office of Women's Empowerment, Child Protection, Population Control and Family Planning has the task of solving problems that often occur in cases of domestic violence (KDRT) against someone, especially women, which results in physical, sexual, psychological, and/or misery or suffering. household neglect including threats to commit acts, coercion, or unlawful deprivation of liberty within the household sphere. therefore it is necessary to have an application that can process this data based on age, type of violence and causal factors to be used as information specifically about cases of domestic violence so that it is easier for the community to understand later. This was created to overcome the problem of extracting important information from a data set of domestic violence cases based on the causative factors at the agency using the k-means clustering method which will be built later. From the results of research conducted using a sample of 20 data, it can be concluded that the most common data are in cluster 2 with data on cases of domestic violence (KDRT) based on many causal factors with a total of 7 data and located in the age group (X ) is aged 17-25 years, and for the type of violence group (Y) that is carried out is Abuse and the causal factors (Z) which mostly occur due to External Factors / Divorce.